The Synergies Between Educational Philosophy Streams and Ki Hajar Dewantara's Ideologies in the Mardeka Belajar Curriculum - Hunaepi, Hunaepi; Suastra, I Wayan; Tanjung, Henra Saputra; laia, Bestari; Raharjo, Raharjo (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2023)
The synergy between educational philosophical streams and the thoughts of Ki Hajar Dewantara is crucial in developing the concept of the